(untitled) (IJM: Journal of Multidisiplinary, 2025)
Hypertension is a medical condition that should not be taken lightly, as it carries a high risk of leading to serious complications such as stroke, heart attack, kidney failure, and even ruptured blood vessels in the brain and other vital organs. To reduce the harmful effects of high blood pressure, various approaches have been explored, one of which is non-pharmacological therapy using natural ingredients. Boiled ginger water has proven to be an effective alternative in gradually lowering blood pressure. This approach has been implemented in community nursing care practices for patients with hypertension who experience complaints such as acute pain, sleep disturbances, and a lack of understanding about their health condition. Through regular consumption of boiled ginger water, the results have been promising showing a significant drop in blood pressure from 170/100 mmHg to 120/80 mmHg within just four days. This success not only highlights the effectiveness of natural remedies but also emphasizes the crucial role of nurses in providing health education. Ginger water therapy can serve as a simple, safe, and cost-effective option for long-term hypertension management, as long as it is carried out consistently and accompanied by proper monitoring.